A comparative study of velocity reduction on feather and synthetic shuttlecocks using corrected initial velocity during an overhead smash - Rusdiana, A.; Pramutadi Andi Mustari, A. (Sport Science - International Scientific Journal of Kinesiology, 2017)
In this study, the flight performance of three shuttlecock models from different companies, one made with feather material and the others with nylon (plastic), were investigated during an overhead smash. Overhead smash is a complex condition where high velocity takes place. The shuttlecock is aerodynamically shaped and has low mass, thus it decelerates very quickly as it flies in the air due to the drag force of the air. Since understanding in the area of a high-speed situation during overhead smash is limited, the main objective of this study is to conduct a comparative analysis of natural feather and synthetic shuttlecock velocity reduction using a regression equation to obtain initial velocity. Method: This study involved righthanded, 20-years-old university badminton players, with a 1.72m in height, weighing 60kgs. After a general and a specific badminton warm-up, the subjects were asked to hit eight shuttlecocks with a maximal speed smash shot. The shuttlecock trajectory was recorded using a high-speed video camera (Phantom Miro-eX2, USA) set at 200 frames/sec and 1/2000 exposure time. The camera was positioned at the right-centre side of the badminton court, so that the optical axis of the camera lens was almost perpendicular to centre of the net position, with an approximate horizontal distance of 22m. The cork of shuttlecock was digitized using Frame DIAZ IV software analysis. Results: The present investigation has developed a regression approach based calculation for obtaining initial velocity during an overhead smash. This approach enables the determination of racquet-shuttlecock impact position and initial velocity for the overhead smash whilst overcoming the difficulties present. Thus, the material of the head had a high possibility of affecting its initial velocity. Since the test was conducted using the same racquet for every trial, thus the effect of the restitution of the racquet strings can be eliminated. Conclusion: The calculation of initial velocity (after impact) using the regression approach was successfully conducted. The comparison shows that the nylon Mizuno shuttlecock had the highest velocity reduction after certain distances (5 and 9 m). Feather and nylon Gosen have similar initial velocity. However, the nylon Gosen was less affected by air restriction (drag force) in comparison to the feather one.